2016
DOI: 10.1021/jacs.5b12680
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Isotope Editing of Proteins for Site-Directed Vibrational Spectroscopy

Abstract: Vibrational spectra contain unique information on protein structure and dynamics. However, this information is often obscured by spectral congestion, and site-selective information is not available. In principle, sites of interest can be spectrally identified by isotope shifts, but site-specific isotope labeling of proteins is today possible only for favorable amino acids or with prohibitively low yields. Here we present an efficient cell-free expression system for the site-specific incorporation of any isotop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 47 publications
6
24
0
Order By: Relevance
“…30 Recently, Peuker et al showed that non-natural isotope labels can be included in large proteins using cell-free expression. 89 These latter two methods are extremely exciting, as they have opened the door to isotope labeling proteins regardless of size.…”
Section: Theory Of 2d Ir Spectroscopymentioning
confidence: 99%
“…30 Recently, Peuker et al showed that non-natural isotope labels can be included in large proteins using cell-free expression. 89 These latter two methods are extremely exciting, as they have opened the door to isotope labeling proteins regardless of size.…”
Section: Theory Of 2d Ir Spectroscopymentioning
confidence: 99%
“…with amino acids, nucleotides, salts and an energy regeneration system ( Figure 2). [20,21,28,30,31] It is important to mention that, once used, the tRNA CUA cannotb er eloaded inside the CF reaction, making this process ao ne-off reaction.…”
Section: Nonsensesuppression For Unnatural and Natural Amino Acidsmentioning
confidence: 99%
“…[30] More recently,t he green fluorescent protein (GFP) was produced with as ingle [ 13 C, 18 O]tyrosine. [31] The sample enabledt he recording of timeresolved infrared absorption spectra in as ite-specific manner and yieldedn ovel information on the photodynamicso fG FP. Despite these successful examples, when aiming to use isotopically labeled canonical amino acids, the synthesis of large quantities of the aminoacylated dinucleotides presentsa ni mportant bottleneck.…”
Section: Strategiestol Oad Trna Cuamentioning
confidence: 99%
See 2 more Smart Citations